(untitled) (Fiep Bulletin - online, 2014)
The osteoarthritis is a chronic disease, which leads to multiple functional incapacity progressive, with pain presence influencing the functional activity level. The aim of this study was to evaluate the effect of laser, 660 nm, in the development of pain and swelling in rats subjected to experimental osteoarthritis. Ten female rats were used, divided into two groups: GS-induction of arthritis in the right knee and sham treatment; GL-induction of arthritis in the right knee and laser irradiated with 10 J / cm². For the induction of arthritis was injected 0,1 ml of Freund Complete Adjuvant of the femoral-tibial articular space. The pain evaluation occurred through Paw Elevation Time (PET), when the animal walking for one minute in a metal cylinder in motion, at times before injury, after 10 days of the injection, after the 5th therapy, prior to 6th therapy and the end of the 10th therapy. The edema evaluation was performed with metallic caliper medium-laterally to the knee joint, at times similar to PET. Treatment with laser began in the 10th day after the arthritis induction on the medial interline joint. The procedure was daily, for 10 days, intervals of two days between the 5th and 6th sessions. The results showed that for PET to GS there was significant increase after injury, with a tendency to increase in subsequent time, without signficant diminishing compare post-injury with subsequent moments, to GL there was increased in the post-injury, which decreased significantly in subsequent periods. For the edema, GS presented significant appearance of it, which has not diminished; for GL the edema was also present, but there was a significant reduction of the same. We concluded that the laser produce effects on pain and edema, with diminishing of them.